ECOLOGICAL HUMANISM: CONTEXTUAL ANALYSIS OF THE MAKKIYAH AND MADANIYAH VERSES: Exploring Environmental Ethics in Qur’anic Revelation Stages - Hanna, Hanna Juairiyah Isnaini; Syefriyeni; Halimatussa’diyah (Program Studi Ilmu Al-Qur’an dan Tafsir, Fakultas Ushuluddin, Universitas Annuqayah (UA), 2025)
Environmental degradation caused by uncontrolled modernization and development poses a significant challenge for humanity today. Within this context, Islamic teachings -particularly the Qur’an- offer substantial potential in providing ethical and spiritual paradigms to preserve ecological balance. This research addresses the issue through an ecological humanism approach, integrating humanitarian values with environmental concern, analyzed via the contextual study of Makkiyah and Madaniyah verses in the Qur’an. The aim is to explore how the Qur’an holistically frames the human–nature relationship across two sociologically and historically distinct phases of revelation. A qualitative method is employed, combining thematic interpretation and contextual analysis. Primary data consists of Qur’anic verses addressing ecological issues such as climate change, biodiversity, pollution, water scarcity, sustainable agriculture, and renewable energy. The tafsir works Al-Misbah and Al-Jalalain serve as key references for contextual interpretation. Findings indicate that Makkiyah verses establish a theological foundation and foster transcendent ecological awareness, while Madaniyah verses emphasize practical applications through social ethics and environmental governance. Together, these two bodies of revelation create a synergistic paradigm of ecological humanism that remains relevant in addressing today’s environmental crises. In conclusion, the Qur’an is not merely a spiritual text but also a profound ethical framework for cultivating sustainable ecological awareness, affirming Islam’s role as a mercy to all creation (rahmatan lil ‘ālamīn).